2008
DOI: 10.1029/2008jc005004
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Aperture Radar observations of resonantly generated internal solitary waves at Race Point Channel (Cape Cod)

Abstract: Synthetic Aperture Radar images revealed the two‐dimensional propagation characteristics of short‐period internal solitary waves in Race Point Channel in Massachusetts Bay. The images and in situ measurements of the flow in the channel are used to infer the likely generation mechanism of the waves. The solitary waves are generated during the ebb phase of the tide within the channel. On some occasions, two trains of internal waves are generated presumably at the same location but at slightly different phases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Both up-and downstream traveling SIWs can be generated during the acceleration or deceleration phase of the tide. Da Silva and Helfrich (2008) have observed such generation of SIWs during both the accelerating and decelerating phase of the tide in Race Point Channel. Bogucki et al (1997) found resonantly generated SIWs in a stratified bottom layer in the California shelf, which significantly contributed to vertical mixing.…”
Section: Internal Wavesmentioning
confidence: 95%
“…Both up-and downstream traveling SIWs can be generated during the acceleration or deceleration phase of the tide. Da Silva and Helfrich (2008) have observed such generation of SIWs during both the accelerating and decelerating phase of the tide in Race Point Channel. Bogucki et al (1997) found resonantly generated SIWs in a stratified bottom layer in the California shelf, which significantly contributed to vertical mixing.…”
Section: Internal Wavesmentioning
confidence: 95%
“…However, the wave packets are irregularly spaced rather than exhibiting typical semidiurnal wavelengths as observed in other coastal regions (e.g., Jackson, 2004;da Silva et al, 2009;Magalhães and da Silva, 2012). It is also interesting to note that numerical models show little or no semidiurnal IW energy in this region (e.g., see Figure 4 in Buijsman et al, 2016).…”
Section: Resonant Generation Of Iwsmentioning
confidence: 94%
“…Comparable variability of the order of 20 cm s -1 is also found at shallow depths within a springneap tidal cycle, which decreases to almost zero beyond 2,000 m depth. This means that two different flows (i.e., MC and tides) are constantly interacting in the study region, resulting in strong stratified currents flowing over irregular bottom bathymetry-known conditions for significant IW activity, as shown for other coastal regions (e.g., Bogucki et al, 1997;Farmer and Armi, 1999;da Silva and Helfrich, 2008;Lentini et al, 2016).…”
Section: Study Regionmentioning
confidence: 99%
“…Numerical solutions (2-dimensional Navier-Stokes equations) of the initial value dam-break problem are used to test the theoretical results. Da Silva and Helfrich (2008) examined the generation of nonlinear internal waves by tidal flow though a channel. From satellite remote sensing imagery and some in situ current data from Race Point Channel (Cape Cod), it is found that two packets can be generated on a single ebb tide due to a novel double passage through resonance mechanism.…”
Section: Work Completedmentioning
confidence: 99%
“…One packet is formed on each ebb or flood phase of the tide with the two packets propagating in opposite directions. Recently analysis of Synthetic Aperture Radar images and in situ flow data revealed a novel mechanism in which two packets (propagating in the same direction) may be generated on a single ebb phase of the tide through Race Point Channel in Massachusetts Bay (da Silva and Helfrich, 2008). The images and in situ measurements of the flow in the channel are used to infer the generation mechanism of the waves within the Channel.…”
Section: Figure 4 Numerical Solutions Of the Navier-stokes Equationsmentioning
confidence: 99%